Communication of the Built Environment - Boštjan Bugarič (Igra Ustvarjalnosti, 2017)
How do we react to different ways of communicating built environment? How do podcasts (sounds), documentaries (images) and social media communicate ideas and concepts often reaching diverse audiences? Drawing on examples of how different knowledge can be communicated through sound (podcast), images (documentary film) and catalogues (social media) we will reflect on how to create spaces that cater for different audiences and the meaning of disseminating built environment research in formats other than design. We will walk through the markets of London, explore unfinished buildings in Koper and look at digitized Architectuul's online catalogue. Different ways of communication involve different focus groups and methods of public involvement. Which communication enables the creation of a critical urban discourse depends on the access to the target public.